A környezetgazdaságtan és a regressziós diszkontinuitás. A klímagazdaságtan színe és visszája.: Environmental Economics and Regressive Discontinuity The two sides of Climate Economics - Kerekes, Sándor (Közép-Európai Közlemények, 2020)
Climate change has become common talk, one visible sign of it is how significantly green parties gained strength across Europe. Few people deny anymore the fact of climate change, but opinions vary greatly about how to solve the problem. Economics, even practitioners discuss the problem, and provide new ideas to the growing academic literature on the subject. At long last climate change and the energy problem has reached the threshold of public awareness. Just as renewable energy, climate economics has now become a mainstream topic. While I find it important that in 2018 a climate economist, William Nordhaus, was awarded the Nobel Price, my joy is not cloudless. The results of Nordhaus’ DICE model and the 1,5 Co aim of the U.N. are completely out of touch with each another. The current paper examines this entire issue.